Rheumatoid Arthrities: Etiology Pathophysiology and Modern Treatments - Deepak Chandra Joshi; Harshita; Angana Naskar; Kunal Datta; Urmistha Sarkar; Mihir Kedarbhai Otia; Tania Khatoon (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease that affects the joints. Age, gender, genetics, and environmental exposure are all factors (cigarette smoking, air pollutants, and occupational). If untreated, felty syndrome, rheumatoid vasculitis, and irreversible joint damage might occur, necessitating splenectomy. Because there is no cure for RA, treatment seeks to reduce pain and prevent further damage. To develop effective RA treatments, researchers must first understand how the disease advances in people and how pathogenic pathways influence this progression. Modern pharmacologic therapy have made tremendous progress in obtaining illness remission without joint deformity (including conventional and biological treatments as well as novel potential small-molecule disease-modifying drugs). Despite this, many RA patients do not respond well to conventional treatments, necessitating the development of novel drugs. This comprehensive review of current advancements covers RA causation, disease-modifying drugs, and prospective RA therapeutics. This section summarises the various RA-related therapies available in the past and now.